SMARTBAND TRACKER UNTUK ANAK USIA DIBAWAH 6 TAHUN MENGGUNAKAN WEMOS D1 DENGAN MONITORING MELALUI SMARTPHONE - Dhea Syafitri; Aryanti Aryanti; Muhammad Zakuan Agung (JURNAL TELISKA, 2025)
Smartband tracker is designed to monitor the child's location directly through the blynk application on the smartphone. To make this smartband requires several components, namely the Wemos D1 Mini as the brain center of the smartband control device, GPS is used to determine the position point of the child's whereabouts, the battery functions as a power supply so that the smartband can operate independently, the Battery Mangament System functions as a backup battery life and the Switch is used as an On / Off button. This tool works in a way, if the red LED flashes it means the GPS has obtained a coordinate point where the results can be seen in the blynk application which can display the location point of the child's whereabouts, displaying coordinate points such as latitude, longitude, and speed. In this study, testing was carried out at 5 location points. The results of the study showed that speed variations were greatly influenced by the duration and intensity of movement, not only by the distance traveled. High speed is recorded at short distances when fast movement occurs, namely point 1 to point 6, while low speed occurs even though the distance is long, when the movement is slow, namely at point 1 to point 5. After testing the tool, the results show that the smartband can work well and can determine the location point in real-time and the advantage of this tool is that it has a buzzer feature that can be turned on via the blynk application on the smartphone where this buzzer will make a sound when activated. Key words : Smartband, IoT, Wemos D1, GPS Tracker, Children, Smartphone, Monitoring